1996
DOI: 10.3168/jds.s0022-0302(96)76598-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Amino Acid Infusion on Leucine Oxidation Across the Mammary Gland of the Lactating Goat

Abstract: Changes in the kinetics of leucine in the mammary gland were examined in four lactating goats (25, 38, 45, and 135 DIM) that were given an i.v. infusion of a mixture of 18 AA, not including leucine, to alter the availability of leucine to the gland relative to other AA. Arteriovenous monitoring of [1-13C]leucine kinetics across one-half of the mammary gland was conducted on the last day (d 6 or 7) of the saline (control) and the AA infusion periods. Although blood flow to the mammary gland and the arterial con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 22 publications
6
47
1
Order By: Relevance
“…It has been suggested that it is not blood AA concentrations per se that limits milk protein production, but rather the metabolic machinery which determines maximum velocity of milk protein production (Cant et al, 2001) or a gastrointestinal event (Bequette et al, 1996), both of which are under hormonal control.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that it is not blood AA concentrations per se that limits milk protein production, but rather the metabolic machinery which determines maximum velocity of milk protein production (Cant et al, 2001) or a gastrointestinal event (Bequette et al, 1996), both of which are under hormonal control.…”
Section: Discussionmentioning
confidence: 99%
“…Even though both lysine and leucine are taken up in excess of requirements, mainly to oxidize and synthesize other AA, Lapierre et al (2009) suggested that excess uptake of lysine across the mammary gland was required to maintain milk protein production while leucine oxidation decreased if leucine supply was limited, thereby indicating that excess leucine is not required to sustain milk protein yields. Bequette et al (1996) reported that increasing the supply of leucine to the mammary gland did not enhance milk protein output, but did increase its oxidation in the mammary gland. Lapierre et al (2002) also showed that only 0.16 of the increased supply of leucine available for absorption ended up in milk protein.…”
Section: Potential Impacts Of Differences In Dietary Aa Profilementioning
confidence: 99%
“…In the current study, uptake was calculated from free plasma AA concentrations alone and the peptide-bound AA that might contribute to the mammary tissue metabolism was not considered. Up to 16% of Lys secretion in milk was contributed from plasma peptides in lactating goats at different stages of lactation (Bequette et al, 1996;Mabjeesh et al, 2000). Interestingly, this fraction was not affected by the availability of free Lys in plasma.…”
Section: Discussionmentioning
confidence: 94%
“…A third point that should be borne in mind that these balance measurements across the mammary gland were done under the assumption that AA are taken up by the gland and contribute to a biosynthetic pathway (anabolism). The oxidative pathway was activated in the mammary gland of goats when surplus EAA (e.g., Leu, Lys), relative to requirements, were supplied intravenously (Bequette et al, 1996;Mabjeesh et al, 2000). Up to 31% of the Lys taken up by the gland during LM infusion was oxidized (Mabjeesh et al, 2000).…”
Section: Discussionmentioning
confidence: 99%